2018
DOI: 10.1016/j.addbeh.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and age-varying associations of sensation seeking and substance use across young adulthood

Abstract: Introduction: Sensation seeking is associated with elevated risk for substance use among adolescents and young adults. However, whether these associations vary across age for young men and women is not well characterized. Methods: Using data from the Monitoring the Future (MTF) panel study, we examine the age-varying associations of sensation seeking and three types of substance use behavior (binge drinking, cigarette use, and marijuana use) across ages 18 to 30 using time-varying effect modeling. Analyses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 47 publications
7
19
2
Order By: Relevance
“…Among men, having a moderate to high willingness to engage in/accept health risks was found to be a barrier for CRC screening. This nding is in line with prior studies indicating that a personal disposition like sensation-seeking is associated with more risky health behavior [19].…”
Section: Sample Characteristicssupporting
confidence: 93%
“…Among men, having a moderate to high willingness to engage in/accept health risks was found to be a barrier for CRC screening. This nding is in line with prior studies indicating that a personal disposition like sensation-seeking is associated with more risky health behavior [19].…”
Section: Sample Characteristicssupporting
confidence: 93%
“…That high income was a positive predictor for screening participation in the entire study population as well as in individual educational subgroups is a nding consistent with the literature [7,16,19], but might nevertheless be considered surprising since participation in Denmark is free of charge. It is therefore likely that the in uence of income is not a directly enabling one but might be mediated by differing subcultural norms, concerns and bene t expectations.…”
Section: Discussionsupporting
confidence: 82%
“…An unexpected effect occurred for education. Commonly, a higher level of education has been identi ed as a facilitator for screening participation [7,19], and this was also the case in a prior Danish study based on registry data [16]. In contrast to that, in our study we observed that among the total group as well as in all individual income groups, people with the longest education (more than appr.…”
Section: Discussioncontrasting
confidence: 47%
“…In a behavioral context, men are more into fitness, health risk activities, and sensation seeking, being more indifferent to infectious and contagion signs than women [25,31]. The peak point in health risk behaviors, such as extreme sport, alcohol and drug consumption, driving, and sexual activities undertaken by men has been suggested to correspond to an age of 35 [38], whilst sensation seeking has been suggested to peak in the twenties [39]. On the other hand, women are more concerned about infectious or contagious clues when they are of child-bearing age, pregnant or raising young children, which occurs in younger women [23,30].…”
Section: Discussionmentioning
confidence: 99%